THE INFLUENCE OF APPLICATION FOR LEARNING ARTS MUSIC ON STUDENTS CHARACTERS IN SMA NEGERI 1 SILIMAKUTA - Elsida Aritonang; Elba Frida Silalahi (Grenek: Jurnal Seni Musik, 2019)
From learning of music , SMA Negeri 1 Silimakuta can improve student character. Implementation of character education in schools as part of education reform, the reform of character education can be likened to a tree that has four important parts, which roots, stems, branches, and leaves. The root of the reform is the philosophical foundation (foothold) the implementation of character education must be clear and understood by the community organizers and education practitioners. The trunk of reform is in the form of a mandate from the government as the person in charge of the national education provider. In this case the standards and objectives for implementing character education must be clear, transparent and accountable. This study aims (1) to find out how the Character of Students in SMA N.1 Silimakuta. (2) to find out whether there is an influence of the Application of Music Art Learning to Student Characters in SMA N.1 Silimakuta. This research instrument uses observation, documentation, tests and questionnaires. The test is used to measure student learning outcomes. Questionnaire is used to measure student characteristic variables. The answers to each item of the questionnaire instrument used a Likert scale which have gradations from very positive to very negative. The questionnaire consisted of 30 questions, with four choices of answers from negative to positive given a score of 1.2, 3, and 4. Similar to SMA Negeri 1 Silimakuta, learning in schools also applies character education. Based on data from the results of this study, it was found that the character of students before and after music learning had a significant difference. There is an effect of music learning on student character with an increase in character questionnaire score of 14.01% and an increase in the level of data tendency that is for the very high category increased by 12.93%, for the category quite increased by 27.89% and there was a decrease in the value of the tendency for the less category by 40.82%